Fabrication of anode-supported thin BCZY electrolyte protonic fuel cells using NiO sintering aid. (3rd September 2019) - Lee, Kan-Rong; Tseng, Chung-Jen; Jang, Shian-Ching; Lin, Jing-Chie; Wang, Kuan-Wen; Chang, Jeng-Kuei; Chen, Ting-Chia; Lee, Sheng-Wei
Abstract: A thin and fully dense BaCe0.6 Zr0.2 Y0.2 O3-δ (BCZY) electrolyte for the use of anode-supported protonic fuel cells has been successfully prepared by spin coating using NiO sintering aid. The effects of NiO addition on the electrolyte microstructures and fuel cell performances are also investigated. An appropriate NiO addition has a significant positive contribution to the densification and grain growth of thin BCZY electrolytes. However, too much NiO addition gives rise to NiO aggregation in BCZY electrolyte and deteriorates the cell performance. The enhanced sintering mechanism can be mainly attributed to the oxygen vacancies generated from the NiO decomposition and bulk diffusion of Ni into BCZY perovskites. The fuel cell with a BCZY-3%NiO electrolyte exhibits the highest maximum power density of 106.6 mW/cm 2 at 800 °C among all fuel cells in this study. The electrochemical impedance characteristics of thin BCZY electrolyte fuel cells are further discussed under open circuit conditions. Graphical abstract: Image 1 Highlights: A thin BCZY electrolyte has been prepared by spin coating using NiO sintering aid. The enhanced sintering mechanism can be attributed to increased oxygen vacancies. An appropriate NiO addition promotes the BCZY densification and grain growth. Too much NiO addition gives rise to NiO aggregation in BCZY electrolyte. The cell with a BCZY-3%NiO electrolyte exhibits the highest peak power density.